2016
DOI: 10.1186/s12916-016-0695-2
|View full text |Cite
|
Sign up to set email alerts
|

Undernutrition and malaria in pregnancy – a dangerous dyad?

Abstract: BackgroundIn low-resource settings, malaria and macronutrient undernutrition are major health problems in pregnancy, contributing significantly to adverse pregnancy outcomes such as preterm birth and fetal growth restriction. Affected pregnancies may result in stillbirth and neonatal death, and surviving children are at risk of poor growth and infection in infancy, and of non-communicable diseases in adulthood. Populations exposed to macronutrient undernutrition frequently reside in malaria-endemic areas, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 82 publications
1
22
1
Order By: Relevance
“…The presence of these conditions during pregnancy increases the risk of undernutrition through affecting dietary intake and absorption of nutrients (Barker, Kirkham, Ng, & Jensen, ; Chhoun et al, ; Hurley, Caulfield, Sacco, Costigan, & Dipietro, ; Nguyen et al, ; Teegarden & Bale, ). Malaria, tuberculosis, diarrheal diseases, and other infections highly impact nutritional status of pregnant women in impoverished settings (Papathakis & Rollins, ; Strunz et al, ; Unger, Ashorn, Cates, Dewey, & Rogerson, ; World Health Organization, ). These disease processes increase energy expenditure and protein catabolism, draining nutritional reserves (Unger et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of these conditions during pregnancy increases the risk of undernutrition through affecting dietary intake and absorption of nutrients (Barker, Kirkham, Ng, & Jensen, ; Chhoun et al, ; Hurley, Caulfield, Sacco, Costigan, & Dipietro, ; Nguyen et al, ; Teegarden & Bale, ). Malaria, tuberculosis, diarrheal diseases, and other infections highly impact nutritional status of pregnant women in impoverished settings (Papathakis & Rollins, ; Strunz et al, ; Unger, Ashorn, Cates, Dewey, & Rogerson, ; World Health Organization, ). These disease processes increase energy expenditure and protein catabolism, draining nutritional reserves (Unger et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Malaria, tuberculosis, diarrheal diseases, and other infections highly impact nutritional status of pregnant women in impoverished settings (Papathakis & Rollins, ; Strunz et al, ; Unger, Ashorn, Cates, Dewey, & Rogerson, ; World Health Organization, ). These disease processes increase energy expenditure and protein catabolism, draining nutritional reserves (Unger et al, ). Similarly, depression during pregnancy may also result in maternal undernutrition through engagement in unhealthy behavioural and antenatal practices such as unhealthy eating patterns (Barker et al, ; Teegarden & Bale, ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite recent decline in malaria transmission in Africa, the burden of malaria in pregnancy (MiP) in the absence of adequate prevention remains substantial [3]. In geographical areas with high transmission, the impact of malaria on maternal health depends on age, gravidity, trimester of pregnancy, coinfection [1,4] nutritional status [5] the intensity of malaria transmission (increased in rural populations), season, and use of malaria prevention [6].…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence indicates that the relationship between malaria infection and LBW may depend upon the mother’s nutritional status [ 8 ]. Studies in Papua New Guinea (PNG) and Benin found inconsistent evidence of modification of the malaria infection–LBW relationship by maternal anthropometric status, but studies from Kenya and the Democratic Republic of the Congo (DRC) reported significant modification [ 9 12 ].…”
Section: Introductionmentioning
confidence: 99%